Cidades e exclusão social: o Sul dentro do Sul, o Norte dentro do Sul - Marília Veríssimo Veronese (Ciências Sociais Unisinos)
From the debate sparked by the presentation made by Professor Jaqueline Pólvora, in the first edition of the cycle of Debates Brasil-Cabo Verde, Cities and social exclusion, we seek to make connections with the research project entitled "In search of South epistemologies: knowledge about collective life between groups 'underlings'", which sought to identify the knowledge and social practices produced and experienced by groups considered inferior to the hegemonic logics of hierarchization of knowledge and social recognition. Considering the urban space as a place of production of thinking, practices and modes of subjectivation, concerning groups "underlings", we approach a snip of the project, seeking to understand the North-South relations within the South, i.e. to analyze how a group, inserted in an upper-middle-class neighborhood in Porto Alegre, RS, constructs their representations of collective life, in a territory whose surroundings often proves hostile. From sociopoetics methodology assumptions, we obtained data from the perspective of horizontal construction of knowledge. Hybridization of knowledge and practices with other active urban social movements seems to be the main strength of Silva Quilombo leaders, to make its existence in the city and produce its rights to the city.